2015
DOI: 10.1002/humu.22731
|View full text |Cite
|
Sign up to set email alerts
|

Identification andIn VivoFunctional Characterization of Novel Compound HeterozygousBMP1Variants in Osteogenesis Imperfecta

Abstract: Osteogenesis imperfecta (OI) comprises a heterogeneous group of disorders that are characterized by susceptibility to bone fractures, and range in severity from a subtle increase in fracture frequency to death in the perinatal period. Most patients have defects in type I collagen biosynthesis with autosomal-dominant inheritance, but many autosomal-recessive genes have been reported. We applied whole-exome sequencing to identify mutations in a Korean OI patient who had an umbilical hernia, frequent fractures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
2
22
0
3
Order By: Relevance
“…We identified three novel homozygous BMP1 missense variants affecting highly conserved amino acids located in the catalytic metalloprotease domain, which may thus interfere with the enzymatic activity of the BMP1/tolloidlike protein. Hitherto, four BMP1 missense variants have been reported (Asharani et al 2012;Martinez-Glez et al 2012;Valencia et al 2014;Cho et al 2015;Syx et al 2015). Two of them, c.747C>G p.(Phe249Leu) and c.808A>G p. (Met270Val), are in the same domain as the variants we identified (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We identified three novel homozygous BMP1 missense variants affecting highly conserved amino acids located in the catalytic metalloprotease domain, which may thus interfere with the enzymatic activity of the BMP1/tolloidlike protein. Hitherto, four BMP1 missense variants have been reported (Asharani et al 2012;Martinez-Glez et al 2012;Valencia et al 2014;Cho et al 2015;Syx et al 2015). Two of them, c.747C>G p.(Phe249Leu) and c.808A>G p. (Met270Val), are in the same domain as the variants we identified (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…; Cho et al. ). The phenotypes of those two patients were severe in accordance with the phenotype of our patient harboring the c.818C>T p.(Ala273Val) variant.…”
Section: Discussionmentioning
confidence: 96%
“…Asharani and colleagues found detectable plasma P1CP at levels just below the normal range in two patients with mutations that affected the signal peptide of BMP1, which confirmed that cleavage of the C‐propeptide occurred, suggesting that alternate enzymes facilitated the event. To date, 18 people with OI due to BMP1 mutations have been described . They share some phenotypic features with those with substrate alterations—white sclerae and absence of dentinogenesis imperfecta—but their fracture phenotype is more severe: 28% had fractures in utero or at birth and 85% had fractured by the age of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…*241 T > C; c.2107G > C (p.Glu703Gln)81Heterozygousc. 808A > G (p.Met270Val); c.1297G > T * [16]91Heterozygousc.925delG (p.Asp309Thrfs*54); c.1492G > A (p.Gly498Arg)[11]101Heterozygousc.34G > C (p.Gly12Arg); c.1839delC (p.Asn614Thrfs*188)112Heterozygousc.34G > C (p.Gly12Arg); c.2188dupC (p.Gln730Profs*294)121Heterozygousc.796_797delTT (p.Phe266Argfs*25); c.2108-2A > GThis report*This variant caused exon 10 skipping
Fig. 3Map of the mutations in BMP1 and mTLD.
…”
Section: Discussionmentioning
confidence: 99%